STUDI LITERATUR: ASESMEN OTENTIK DAN BERBASIS KOMPETENSI DALAM PEMBELAJARAN MIPA - Sagara, Komukai Ria; Agustin Hasan, Angga Van; Anggriawan, Dika; Nurjaman, Ginanjar Juang; Kurniawan, Kurniawan; Taufan, Muhammad; Daya, Titis; Suryana, Andri (LPPM Universitas Bina Bangsa, 2026)
Science and mathematics (MIPA) learning requires assessments that not only measure cognitive mastery but also higher-order thinking skills, scientific literacy, and 21st-century competencies. This study conducted a literature review of 21 national and international articles (2017–2025) on authentic and competency-based assessments. The reviewed studies employed various research designs, including Classroom Action Research, quasi-experiments, descriptive qualitative studies, and Research and Development. The analysis focused on the effectiveness of assessments in enhancing student engagement, conceptual understanding, scientific literacy, problem-solving, collaboration, and practical skills mastery. Results indicate that authentic and competency-based assessments are effective; however, their success depends on teacher competence, instrument quality, facility readiness, and digital support. Major challenges include the lack of standardized instruments, time constraints, and limited teacher understanding. The findings highlight the need for the development of standardized instruments, digital assessments, large-scale quantitative studies, and comprehensive teacher training to ensure consistent and effective implementation.